Funerary Landscapes of the Late Antique "oecumene" Contextualizing Epigraphic and Archeological Evidence of Mortuary Practices. Proceedings of an International Conference in Heidelberg, May 30-June 1, 2019 - Ardeleanu, Stefan; Cubas Díaz, Jon C. (Kulturelles Erbe: Materialität - Text - Edition (KEMTE), 2023)
This volume presents the first pan-Mediterranean panorama of Late Antique mortuary practices, combining and contextualizing an abundant dataset of archaeological and epigraphic evidence. In 17 contributions, a group of international specialists discusses funerary evidence from 14 Late Antique landscapes, in order to show the high diversity of microregional and local customs in funerary cultures as well as the significance of global trends. In this volume various new methodological approaches are applied: the materiality of epitaphs and tombs, their visibility, their accessibility, their perception, their setting within shifting spatial environments, as well as their crucial role within social practices. Therefore, this book fundamentally reshapes our understanding of mortuary habits and the commemoration of the dead during the transitional phase of the Long Late Antiquity.